Impact of TiO2 Nanotubes’ Morphology on the Photocatalytic Degradation of Simazine Pollutant - Suhaimy, Syazwan Hanani Meriam; Lai, Chin Wei; Tajuddin, Hairul Anuar; Samsudin, Emy Marlina; Johan, Mohd Rafie (MDPI, 2018)
There are various approaches to enhancing the catalytic properties of TiO2, including modifying its morphology by altering the surface reactivity and surface area of the catalyst. In this study, the primary aim is to enhance the photocatalytic activity by changing the TiO2 nanotubes' architecture. The highly ordered infrastructure is favorable for a better charge carrier transfer. It is well known that anodization affects TiO2 nanotubes' structure by increasing the anodization duration which in turn influence the photocatalytic activity. The characterizations were conducted by FE-SEM (fiend emission scanning electron microscopy), XRD (X-ray diffraction), RAMAN (Raman spectroscopy), EDX (Energy dispersive X-ray spectroscopy), UV-Vis (Ultraviolet visible spectroscopy) and LCMS/MS/MS (liquid chromatography mass spectroscopy). We found that the morphological structure is affected by the anodization duration according to FE-SEM. The photocatalytic degradation shows a photodegradation rate of k = 0.0104 min-1. It is also found that a mineralization of Simazine by our prepared TiO2 nanotubes leads to the formation of cyanuric acid. We propose three Simazine photodegradation pathways with several intermediates identified.